500 things to know about the ancient world - Howitt, Carolyn (Hauppage, NY : Barron's, 2007)
Presents five hundred facts on ancient cultures, arranged in such categories as food and drink, fashion, sport, society, writing, war, animals, death, and the spiritual world.
Includes bibliographical references (p. 152).
5.8
5-8
Keywords: Civilization, Ancient -- Miscellanea -- Juvenile literature; Civilization, Ancient -- Miscellanea; Ancient civilization -- Miscellanea